IMPLEMENTASI MURABAHAH BIL WAKALAH PRODUK PEMBIAYAAN BSI - M. Guffar Harahap; Haidir Haidir; Muhammad Hizbullah (ITB AAS Indonesia Surakarta, 2023)
Analysis is a work process of an effort to observe something in detail by describing its constituent components or compiling these components for further study. While the implementation can simply be interpreted as the implementation or application or expansion of activities that mutually adjust an activity that is planned and carried out seriously based on certain norms to achieve the objectives of the activity. Murabahah Bil Wakalah contract is a sale and purchase where the Islamic financial institution represents the purchase of the product to the customer, then after the product is obtained by the customer, it is given to the Islamic financial institution. The fatwa of the National Sharia Council regarding the granting of wakalah contracts in murabahah transactions is regulated in the fatwa of DSN-MUI/No.04/DSN/MUI/IV/2000, namely